Immunohistochemical determination of Ang-1, Ang-2 and Tie-2 in placentas of sows at 30, 60 and 114 days of gestation and validation through a bioinformatic approach - Fiorimanti, Mariana Rita (2018)
Angiopoietins (Ang-1, Ang-2) participate in vascular development and placental growth, both bind to Tie-2. This study aimed to determine the localization of angiopoietins in placental development of sows by immunohistochemistry and to validate the gene expression during gestation through a bioinformatic approach. Samples were collected from fifteen maternal-fetal interface from approximately 30 (n = 5), 60 (n = 5) and 114 (n = 5) days of gestation for immunohistochemistry. A bioinformatic approach was performed by re-analysis of public datasets to determine the increase or decrease of genes involved in angiogenesis during pregnancy. There was no significant statistical difference of Ang-1 during gestation, although there was a tendency to increase from mid- to term-gestation (P = 0.7680). A notable decrease of Ang-2 was observed from early- to term-pregnancy (P ≤ 0.05), consistent with the gene expression determined through bioinformatics. Furthermore, there were greater abundances of Tie-2 at both early and at term periods, but lesser abundances at mid-gestation (P ≤ 0.05). The bioinformatics approach indicated that genes related to biological processes such as angiogenesis (i.e., development and morphogenesis of blood vessels) were expressed to a greater extent in early gestation as compared with later in gestation. The Ang-1 gene expression related to cell maturation, response to hypoxia and apoptosis, however, increased as gestation period advanced. In conclusion, angiopoietins may have an important role in the vascular development thus ensuring adequate placental growth in sows. The presence of angiopoietins in the trophoblast suggests a specific role for these pro-angiogenic factors in the tissue formation at the maternal-fetal interface.